Depositional, diagenetic and stratigraphic aspects of Macaé Group carbonates (Albian): Example from an oilfield from Campos Basin - Okubo, Juliana [UNESP]; Lykawka, Ricardo; Warren, Lucas Veríssimo [UNESP]; Favoreto, Julia [UNESP]; Dias-Brito, Dimas [UNESP] (FapUNIFESP (SciELO), 2015)
Carbonate rocks from the Macaé Group (Albian) represent an example of carbonate sedimentation related to the drift phase in Campos Basin. This study presents depositional features, integrating them with diagenetic and stratigraphic aspects of the Macaé Group carbonates including the upper part of the Quissamã Formation and the lower part of the Outeiro Formation. Macroscopic analyses in cores and microscopic ones in thin sections allowed the recognition of eleven sedimentary facies - nine of them corresponding to the Quissamã Formation and two of them representing the Outeiro Formation. These facies were grouped into five facies associations. Oolitic grainstones and oncolitic grainstones are interpreted to be deposited in shallow depth probably in shoals above the fair weather wave base. The interbanks between shoals were formed in less agitated waters and characterized by deposition of peloidal bioclastic packstones and wackestones representative of sedimentation in calm waters. Bioclastic packstones and oolitic packstones/wackestones represent allochthonous deposits related to the beginning of the regional drowning that occur in upper Quissamã Formation. Pithonellids wackestones and bioclastic wackestones with glauconite are related to deep water deposits, characteristics of the Outeiro Formation. Post-depositional features revealed the action of diagenetic processes as, micritization, cimentation, dissolution, compaction, dolomitization and recrystallization occurred during the eoand mesodiagenesis phases. Vertical facies analysis suggests shallowing upward cycles stacked in a sequence progressively deeper towards the top (from the Quissamã Formation to the Outeiro Formation).
Keywords: Carbonate rocks; Diagenesis; Facies; Formation; Outeiro formation; Quissamã